2015
DOI: 10.1016/j.engstruct.2015.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and finite element dynamic analysis of incrementally loaded reinforced concrete structures

Abstract: full bibliographic details are credited, a hyperlink and/or URL is given for the original metadata page and the content is not changed in any way. A note on versions:The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP url' above for details on accessing the published version and note that access may require a subscription.For more information, please contact the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 19 publications
4
9
0
Order By: Relevance
“…It was found that the static stiffness E I s can be used to calculate the static deformations but underestimates the stiffness of cracked concrete beams under dynamic excitation E I d (Jerath and Shibani, 1985). Similar results were reported by several authors showing that the dynamic stiffness E I d is remarkably larger than the static stiffness E I s for cracked reinforced concrete beam (Eccles, 1999; Hamad et al, 2015; Maeck et al, 2000; Musial, 2012, 2017; Neild et al, 2003; Pešić et al, 2015; Tan, 2003; Xu and Castel, 2016). Pešić et al (2015) investigated the influence of damage on the dynamic properties of the cracked reinforced concrete beam experimentally and proposed an updated finite element analysis model with static measured elastic modulus and recommended tensile strength (5% of the characteristic compressive strength).…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was found that the static stiffness E I s can be used to calculate the static deformations but underestimates the stiffness of cracked concrete beams under dynamic excitation E I d (Jerath and Shibani, 1985). Similar results were reported by several authors showing that the dynamic stiffness E I d is remarkably larger than the static stiffness E I s for cracked reinforced concrete beam (Eccles, 1999; Hamad et al, 2015; Maeck et al, 2000; Musial, 2012, 2017; Neild et al, 2003; Pešić et al, 2015; Tan, 2003; Xu and Castel, 2016). Pešić et al (2015) investigated the influence of damage on the dynamic properties of the cracked reinforced concrete beam experimentally and proposed an updated finite element analysis model with static measured elastic modulus and recommended tensile strength (5% of the characteristic compressive strength).…”
Section: Introductionsupporting
confidence: 91%
“…Similar results were reported by several authors showing that the dynamic stiffness E I d is remarkably larger than the static stiffness E I s for cracked reinforced concrete beam (Eccles, 1999; Hamad et al, 2015; Maeck et al, 2000; Musial, 2012, 2017; Neild et al, 2003; Pešić et al, 2015; Tan, 2003; Xu and Castel, 2016). Pešić et al (2015) investigated the influence of damage on the dynamic properties of the cracked reinforced concrete beam experimentally and proposed an updated finite element analysis model with static measured elastic modulus and recommended tensile strength (5% of the characteristic compressive strength). Moreover, Musial (2017) studied the effect of the load level on the natural frequency of cracked reinforced concrete beams and observed that the dynamic stiffness of the unloaded cracked beam was higher than that of the loaded cracked beams with ballast masses.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…[15][16][17][18][19], were shown to affect eigenfrequencies), but in the analysis of the results one should separate the decrease in stiffness due to the reduction in the moment of inertia caused by cracking. It should be noted, however, that this may introduce additional errors (besides the ones described in conclusion No.…”
Section: Discussionmentioning
confidence: 99%
“…Other research papers dealing in part with the problem considered here describe the determination of the Young's modulus of concrete on the basis of the longitudinal vibration frequency by means of an analytical procedure [13], and investigations of the dynamic gain in the Young's modulus over time [14]. A substantial number of analyses are devoted to the study of the dynamic flexural stiffness of reinforced concrete beams [10,[15][16][17][18][19], including RC beams strengthened with CFRP materials [20]. Dynamic test methods can also be used to identify defects in reinforced concrete beams [21].…”
Section: State Of the Art -Selected Testsmentioning
confidence: 99%